Study of wave-current coupling on offshore flexible photovoltaic foundation columns - Zhang, Jian; Lou, Yibing (Frontiers in Marine Science, 2024)
Due to the increasingly serious global energy problems, the photovoltaic industry has experienced significant growth. China has dominated this industry, and there is huge potential for future development and market demand. Offshore photovoltaic installations can be installed on a large scale due to China's long coastline, making it an area of great interest. Structures in water subject to complex hydrodynamic loads due to the joint action of wave-current. These loads differ significantly from those produced by conventional waves. In order to simulate the response of the wave-current coupling to the structure and the fluctuation of the slamming load with the position of the foundation column, this article builds a numerical wave tank using FLUENT. The results indicate that the maximum wave force on the structure occurs at a wave incidence angle of 30°. When there is forward current, the wave-current coupled wave height is smaller than the wave height alone, and the period becomes shorter while the wave speed accelerates. Wave force for wave-current coupling is 9.2% greater than that for linear superposition of wave-current. In the range of free liquid surface wave height, the slamming loads gradually increases while the incremental speed decreases for a single foundation column. The foundation column that meets the wave first is larger than the one that meets the wave later at the same height. However, the blocking effect of the front foundation column and the height difference do not have the same magnitude of influence on the slamming loads.